2005
DOI: 10.1111/j.1445-5994.2005.00935.x
|View full text |Cite
|
Sign up to set email alerts
|

Climatic, high tide and vector variables and the transmission of Ross River virus

Abstract: This report assesses the impact of the variability in environmental and vector factors on the transmission of Ross River virus (RRV) in Brisbane, Australia. Poisson time series regression analyses were conducted using monthly data on the counts of RRV cases, climate variables (Southern Oscillation Index and rainfall), high tides and mosquito density for the period of 1998-2001. The results indicate that increases in the high tide (relative risk (RR): 1.65; 95% confidence interval (CI): 1.20-2.26), rainfall (RR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 15 publications
4
48
0
Order By: Relevance
“…It is possible that the humidity variations in Darwin will prove difficult to model because of what Tong and associates termed "threshold theories" (Tong et al 2004). So far only two published articles have incorporated climatic factors together with vectors into predictive models for RRV infections (Tong et al 2005, Woodruff et al 2006). All the literature and models described in this article reflect the dearth of information from the Northern Territory, the region with the highest incidence rates of RRV and BFV in Australia (Communicable Diseases Australia 2006b, Whelan et al 1997.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that the humidity variations in Darwin will prove difficult to model because of what Tong and associates termed "threshold theories" (Tong et al 2004). So far only two published articles have incorporated climatic factors together with vectors into predictive models for RRV infections (Tong et al 2005, Woodruff et al 2006). All the literature and models described in this article reflect the dearth of information from the Northern Territory, the region with the highest incidence rates of RRV and BFV in Australia (Communicable Diseases Australia 2006b, Whelan et al 1997.…”
Section: Discussionmentioning
confidence: 97%
“…Early analysis of RRV disease tested the relationships between vectors and RRV disease, or climatic variables and RRV, including humidity, temperature, rainfall, and tidal conditions (Gatton et al 2004, Jones et al 1991, Tai 1992, Tong and Hu 2001, Whelan et al 2003. More recently both vector and climatic data have been incorporated into the same models (Tong et al 2005, Woodruff et al 2006. Lags have been employed to account for virus/mosquito lifecycle, incubation period in the human host, and presentation to a medical practitioner.…”
Section: Models Of Rrv and Bfv Diseasementioning
confidence: 99%
“…Other modeling that is relevant includes research on the relationship between mosquitoes and other variables that are likely to be affected by climate change. An example is research into Ross River virus in Queensland, Australia whereby relationships are shown between the disease and climate (especially rainfall) and tides (sea level) Tong et al 2005), climatic variability (Tong and Hu 2002;Tong et al 2004) or all of these (Naish et al 2006). Crane et al (2005), in the context of chemical control of insects, developed a risk model for climate change and its impacts on insect-borne disease.…”
Section: Climate Changementioning
confidence: 99%
“…Because RRV infection is the most common and widespread mosquito-borne disease in Australia, there has been an increasing research interest in the assessment of major determinants of RRV transmission (Hu et al 2004, 2006a, 2006b; Jacups et al 2008, Kelly-Hope et al 2004a; Tong et al 2002, 2005; Woodruff et al 2006). To identify current knowledge gaps and research needs, we critically reviewed the impact of climatic, social, and environmental variability on the transmission of RRV disease.…”
mentioning
confidence: 99%